Answer:
the percentage of men over 50 who wear watches are 61.82%
Step-by-no step explanation:
first just multiply 275 the number of people over 5o then divide it by .6 to get 165 is the answer
i hope this is correct
Answer:
Options A, D and E.
Step-by-step explanation:
Formula to calculate the volume of the triangular prism is,
Volume of the triangular prism = (Area of the triangular base)×(height)
= B × h
Area of the right triangular base = ![\frac{1}{2}(\text{Base})(\text{height})](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28%5Ctext%7BBase%7D%29%28%5Ctext%7Bheight%7D%29)
= ![\frac{1}{2}(8)(14)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%288%29%2814%29)
= 56 m²
Volume of the prism = ![(56)(7)](https://tex.z-dn.net/?f=%2856%29%287%29)
= 392 cubic meter
Therefore, from the given options correct options are Option A, Option D and Option E.
<span>work out the difference (increase) between the two numbers you are comparing.Increase = New Number - Original Number.Then: divide the increase by the original number and multiply the answer by 100.% increase = Increase ÷ Original Number × 100.</span>
When y varies inversely as x it can be expressed as follows:
![\frac{1}{x}\text{ }\propto\text{y}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%7D%5Ctext%7B%20%7D%5Cpropto%5Ctext%7By%7D)
If we write the general equation for this
![y=\frac{A}{x}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7BA%7D%7Bx%7D)
When y=3 and x=4 we can calculate de value of A
![\begin{gathered} x=4 \\ y=3 \\ 3=\frac{A}{4} \\ A=4\cdot3 \\ A=12 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%3D4%20%5C%5C%20y%3D3%20%5C%5C%203%3D%5Cfrac%7BA%7D%7B4%7D%20%5C%5C%20A%3D4%5Ccdot3%20%5C%5C%20A%3D12%20%5Cend%7Bgathered%7D)
Then the equation that describes an inverse variation between x and y is_
Answer:
a(10) = 3^9 = 19683
Step-by-step explanation:
In this sequence each new term is equal to 3 times the previous term. Thus, 3 is the common ratio. The first term is 1.
The general formula for the nth term of a geometric sequence i
a(n) = a(1)*r^(n -1), where r is the common ratio.
Here, a(n) = 1*3^(n - 1), and so
the 10th term is
a(10) = 1*3^(10 - 1), or
a(10) = 3^9 = 19683